PEMBELAJARAN BAHASA ARAB BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS - Yachya, Abdillah (Albariq: Jurnal Pendidikan Bahasa Arab, 2024)
The study aims to evaluate the effectiveness of project-based Arabic learning in improving students' critical thinking skills. The research used a qualitative approach with the design of a case study involving 30 madrasah aliyah students. Data is collected through in-depth interviews, participatory observations, and analysis of project documents. Research results show that project-based learning encourages student active involvement, improves learning motivation, and develops critical thinking skills. Students showed improvements in analytical, problem-solving, and communication skills. In addition, this approach also develops social skills such as cooperation and intercultural competence. This finding supports a constructivist theory that emphasizes the importance of active and contextual learning. Research recommendations include training for teachers in project-based learning methods and development of more varied projects to enrich student learning experiences. Overall, project-based Arabic learning has proven to provide broad benefits in the context of education in the era of globalization.